SPILLOVER EFFECT INFLASI DAGING SAPI ANTAR KOTA: APLIKASI METODE BEKK-GARCH UNTUK JAKARTA, SALATIGA, DAN SURABAYA - Ribut Nurul Tri Wahyuni; Nasrudin Nasrudin (MEDIA STATISTIKA, 2020)
Beef consumption in Indonesia tends to increase and its price fluctuates. In addition to internal factors, the volatility of beef inflation can also be influenced by other regions (spillover effect). Using BEKK-GARCH model, we try to show spillover effect the volatility of beef inflation in Jakarta, Salatiga, and Surabaya. The transmissions of news effects occur from Jakarta and Surabaya to Salatiga and from Jakarta and Salatiga to Surabaya. Transmission of two-way volatility occurs between Jakarta and Surabaya. Furthermore, the transmission of one-way volatility occurrs from Jakarta to Salatiga. Price fluctuation in consumer areas will be followed by price fluctuation in other consumer areas and producer areas. Therefore, controlling beef inflation should be began from consumer areas.